Analisis Konflik Batin Dan Mekanisme Pertahanan Tokoh Sasaki Miyo Dalam Anime Nakitai Watashi Wa Neko Wo Kaburu - Nurul Annisa Sabrina (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2021)
This research examines the intrinsic elements of anime Nakitai Watashi wa Neko wo Kaburu, as well as the inner conflicts and defense mechanisms of Sasaki Miyo character in the anime Nakitai Watashi wa Neko wo Kaburu. This research uses qualitative descriptive technique with literary psychology approach. The data collection technique was carried out by using the note-taking technique. The theories that were used in this research are fiction study theory to analyze intrinsic elements and Freud's psychoanalytic theory to analyze the inner conflict and defense mechanisms of Sasaki Miyo. The result of this research is that there are 35 data that show the intrinsic elements of the anime Nakitai Watashi wa Neko wo Kaburu and 8 data that show the inner conflict and defense mechanisms of Sasaki Miyo character in the anime Nakitai Watashi wa Neko wo Kaburu. The conclusion that can be drawn from this research is that Sasaki Miyo, a middle school girl who was unhappy because her parents had gotten divorced and chose to run away from her house as a cat, experienced inner conflicts and used various defense mechanisms when the inner conflicts occurred. There are 6 defense mechanisms that are used by Miyo, and those are reaction formation, rationalization, reversal, compensation, and undoing. The factors that cause Miyo's unhappiness eventually accumulated so that Miyo often used projection as a defense mechanism, where she continued to project her anger towards her parents.